EDUKASI PEMANFAATAN LIMBAH ORGANIK SEBAGAI ECO-ENZYME UNTUK PRODUK KESEHATAN BAGI MASYARAKAT RAWA KOPI-DEPOK (Jurnal Bakti Masyarakat Indonesia, 2024)
Waste from the production process in the community around Rawa Kopi, Depok, is one of the problems in their environment that requires further processing. Eco-enzyme is a potential organic waste processing technology and can be an effort to achieve the 12th SDGs goal regarding sustainable production and consumption patterns. This technology involves a fermentation process of organic waste combined with brown sugar/molasses and air in a certain ratio. The eco-enzyme liquid produced is an active ingredient that can be used for various purposes. This community service activity aims to provide outreach and education in utilizing waste, especially organic waste, which can be processed into eco-enzymes for the community around Rawa Kopi, Depok. The activity began with giving a pretest, then socialization about eco-enzymes through lectures and interactive discussions. Evaluation is carried out on the process, including attendance, enthusiasm/enthusiasm, participants' responses to training activities, and post-test material education. The results of the activity will provide knowledge to utilize organic waste around us into eco enzymes, which can then be further utilized into materials such as fertilizer, disinfectant, hand sanitizer and others. Community knowledge and understanding in utilizing organic waste around us into eco enzymes can increase after the activity. The results of the activity were able to provide knowledge about degenerative diseases and the use of Indonesian medicinal plants for degenerative diseases. Community knowledge and understanding of degenerative diseases and recognizing and utilizing plant medicines can increase significantly (p